Chemopreventive and Anticancer Role of Resveratrol against Oral Squamous Cell Carcinoma - Giuseppe Angellotti; Giulia Di Prima; Elena Belfiore; Giuseppina Campisi; Viviana De Caro (MDPI AG, 2023)
Oral squamous cell carcinoma (OSCC) is one of the most prevailing and aggressive head and neck cancers, featuring high morbidity and mortality. The available conventional treatments suffer from several adverse effects and are often inefficient in terms of their survival rates. Thus, seeking novel therapeutic agents and adjuvants is of the utmost importance for modern society. Natural polyphenolic compounds have recently emerged as promising chemopreventive and anticancer agents. Specifically, the natural compound resveratrol (RSV) has recently gained momentum for this purpose. RSV is useful for treating OSCC due to its antiproliferative, antimetastatic, and proapoptotic effects. Additionally, RSV acts against tumor cells while synergically cooperating with chemotherapeutics, overcoming drug resistance phenomena. Despite these wide-spectrum effects, there are few specific investigations regarding RSV's effects against OSCC animal models that consider different routes and vehicles for the administration of RSV. Interestingly, an injectable RSV-loaded liposome-based formulation was proven to be effective against both in vitro and in vivo OSCC models, demonstrating that the development of RSV-loaded drug delivery systems for systemic and/or loco-regional applications may be the turning point in oral cancer treatment, leading to benefits from both RSV's properties as well as from targeted delivery. Given these premises, this review offers a comprehensive overview of the in vitro and in vivo effects of RSV and its main derivative, polydatin (PD), against OSCC-related cell lines and animal models, aiming to guide the scientific community in regard to RSV and PD use in the treatment of oral precancerous and cancerous lesions.